Arterial hypertension in childhood: a literature review (Research, Society and Development, 2021)
Arterial Hypertension (AH) is a clinical condition characterized by a sustained increase in blood pressure levels, commonly investigated in the adult population. However, arterial hypertension in childhood and adolescence, defined by systolic and/or diastolic blood pressure values equal to or greater than the 95th percentile for sex, age and height on three or more different occasions is rarely investigated. In this context, recent evidence points to a correlation between the increase in blood pressure (BP) in childhood and adolescence, especially from the age of 6, with the growth of the obesity epidemic in this population range. In addition, it is recommended that children above 3 years old have their BP checked at least once a year, and in all medical visits if they present at least one of the risk factors for hypertension. Therefore, clinical practice guidelines recommend that a diagnosis be established when identical BP values are found on three separate visits, with such values being equal to or greater than the 95th percentile. As the evidence points out, AH constitutes its pillars in the first years of life of the individual, attesting that high blood pressure levels in this age group are strong predictors of this condition in adults, this is the focus of this review.